Single-side knitted fabric

By using multi-layer structure and yarn containing inorganic particles in knitted fabrics, combined with the co-weaving design of A-layer and B-layer yarn, the problem of difficult water marks and not dry enough when sweating a lot of time is solved, and the comprehensive effect of waterproof marks, dryness, water absorption and fast drying and anti-shield are achieved.

CN119640475APending Publication Date: 2025-03-18TORAY FIBER RES INST(CHINA) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311203749.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-18
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing knitted fabrics are difficult to hide when sweating a lot, and the skin is not dry enough, and the anti-slit properties are insufficient.

Method used

A single-sided knitted fabric consisting of A layer, B layer and C layer is used. The C layer has an uneven structure. The yarn of A layer contains more than 8.0% by weight inorganic particles. The yarn of A layer and B layer are knitted together in the tissue cycle to form a tight coil arrangement, which satisfies the specific relationship between the accumulation of horizontal and vertical density and the yarn breaking strength.

Benefits of technology

It is achieved that water traces are not easy to see after sweating, keep the muscle surface dry, has good water absorption and rapid drying, and has excellent anti-slide performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640475A_ABST
    Figure CN119640475A_ABST
Patent Text Reader

Abstract

The invention discloses a single-side knitted fabric. The fabric is composed of a layer A, a layer B and a layer C. The layer C is of a concave-convex structure. In one weave cycle, at least one transverse row is formed by jointly weaving yarns of the layer A and yarns of the layer B in the same weaving mode, the yarns of the layer A comprise yarns A1 containing more than 8.0 wt% of inorganic particles, loops formed by A1 account for more than 30% of the total number of loops of the layer A, and the yarns of the layer B account for more than 30% of the total number of loops of the layer A. The product J of the transverse density and the longitudinal density of the fabric and the breaking strength Q of the yarns A1 meet the following relational expression: J / Q is greater than or equal to 1200. The single-side knitted fabric is good in water mark prevention effect, water marks cannot be seen easily after sweating, the muscle surface can still be kept dry and comfortable when a large amount of sweating occurs, water absorption and quick-drying performance is good, snagging resistance is excellent, and the single-side knitted fabric is particularly suitable for being made into sports shirts, T-shirts or POLO shirts and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a knitted fabric, in particular to a single-sided knitted fabric which is not easy to see water marks after sweating, can keep the skin surface dry when sweating heavily, and has good anti-snagging property. Background Art

[0002] In today's society, consumers have higher requirements for the comfort and functionality of clothing. In a hot and humid environment or after strenuous exercise, the human body sweats a lot, and people expect to develop a knitted fabric that is not easy to see water marks after sweating and can keep the skin dry.

[0003] To this end, people have conducted a lot of research. For example, the patent document JP2019509407A discloses a double-sided knitted fabric, which includes a surface layer and an inner layer, and the surface layer and the inner layer are connected by loops, and the inner layer has a concave-convex structure, and each convex unit has 3 to 10 loops in at least one direction in the horizontal and vertical directions. The fabric has the characteristics of dry contact surface and comfortable wearing, but the problem of embarrassing water marks on the surface of the fabric when sweating a lot has not been solved.

[0004] For example, patent document CN105986358A discloses a water-absorbing and quick-drying knitted fabric and its use. The fabric is a single-sided knitted fabric with a concave-convex structure on the back. The fabric has excellent water-absorbing and quick-drying properties, and the skin surface is dry and cool. However, the problem of embarrassing water marks on the surface of the fabric when sweating heavily has not been solved.

[0005] For another example, patent document CN102134776A discloses a fabric with a two-way regulating function for moisture and heat. The side of the fabric that contacts the skin is the inner layer, which is woven from yarns with a conventional moisture regain of less than 2%; the other side of the fabric is the surface layer, which is woven from yarns with a conventional moisture regain of more than 8%. The inner layer of the fabric adopts a structure that bulges toward the skin side. The fabric can effectively transfer heat and moisture in motion, and has excellent heat preservation and perspiration effects. The bulge height is 0.12 to 1.0 mm. If the bulge height is too large, the wearing comfort of the fabric will be reduced, and the problem of water marks on the surface of the fabric causing embarrassment has not been solved.

[0006] For another example, patent document CN115398051A discloses a knitted fabric and its use, wherein the fabric contains yarn A with an inorganic particle content of 8.0% by weight or more, the weight of yarn A accounts for more than 30% of the total weight of the knitted fabric, and within a complete weave cycle of the knitted fabric, yarn A is arranged on one or both sides of the knitted fabric, and the loops formed by yarn A account for more than 30% of the total loops on the side where it is located. The fabric has excellent anti-watermarking effect, but the weave of the yarn A in the document is prone to the problem of poor snagging, and when sweating heavily, the problem of the fabric surface being sticky and not dry enough has not been solved. Summary of the invention

[0007] The purpose of the present invention is to provide a single-sided knitted fabric which has good anti-water mark effect, is not easy to see water marks after sweating, can keep the skin dry when sweating heavily, has good water absorption and quick-drying properties, and has excellent anti-snagging properties.

[0008] The technical solution of the present invention is as follows:

[0009] The single-sided knitted fabric of the present invention is composed of an A layer, a B layer and a C layer, wherein the C layer has a concave-convex structure, wherein in one tissue cycle, at least one horizontal row is woven together by the yarn of the A layer and the yarn of the B layer and formed in the same weaving manner, the yarn of the A layer includes a yarn A1 containing an inorganic particle content of more than 8.0 weight percent, the coils formed by A1 account for more than 30% of the total number of coils of the A layer, and the product J of the transverse and longitudinal densities of the fabric and the breaking strength Q of the yarn A1 satisfy the following relationship: J / Q≥1200.

[0010] The present invention obtains excellent waterproof trace effect of the fabric by selecting yarn containing a specific content of inorganic particles and limiting the proportion of the loops formed by the yarn on the surface where it is located; in one tissue cycle, at least one horizontal row is formed by the yarn of the A layer and the yarn of the B layer, which ensures the flatness and compactness of the fabric and gives the fabric excellent anti-snagging performance. The single-sided knitted fabric of the present invention is suitable for the field of clothing, and is suitable for making sports shirts, T-shirts, POLO shirts or pants, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 This is a schematic diagram of the cross-sectional structure of the single-sided knitted fabric of the present invention, wherein 1 represents layer A, 2 represents layer B, and 3 represents layer C.

[0012] Figure 2 This is an organizational diagram of Example 1 of the present invention.

[0013] Figure 3 This is the organizational diagram of Example 16 of the present invention.

[0014] Figure 4 This is the organizational diagram of Example 18 of the present invention. DETAILED DESCRIPTION

[0015] The single-sided knitted fabric of the present invention is composed of an A layer, a B layer and a C layer, wherein the C layer has a concave-convex structure, and in one weaving cycle, at least one horizontal row is formed by weaving the yarns of the A layer and the B layer together in the same weaving manner, wherein the outer side of the C layer is the inner layer, and the outer side of the A layer is the surface layer.

[0016] The single-sided knitted fabric of the present invention has at least one horizontal row formed by knitting the yarn of layer A and the yarn of layer B together in one weaving cycle and using the same knitting method. That is, the two yarns form the same horizontal row on the fabric with the same knitting unit. When knitting, the knitting needles of the equipment have the yarn of layer A and the yarn of layer B at the same time and knit together, which is called common knitting; when the knitting needles of the yarn of layer A and the yarn of layer B perform the same knitting action during knitting, it is formed by using the same knitting method. Specifically, it means that when the A layer is all full-loop horizontal rows, the number of horizontal rows formed by weaving the yarns of the A layer and the B layer together into loops accounts for more than 30% of the total number of horizontal rows, and preferably all horizontal rows are formed by weaving the yarns of the A layer and the B layer together into loops; when the A layer is full-loop horizontal rows and non-full-loop horizontal rows, at least the full-loop horizontal rows are formed by weaving the yarns of the A layer and the B layer together into loops, and the number of full-loop horizontal rows preferably accounts for more than 30% of the total number of horizontal rows; when the A layer is all non-full-loop horizontal rows, all horizontal rows are formed by the yarns of the A layer and the B layer together in the same weaving method. The non-full-loop horizontal rows in this article refer to horizontal rows composed of loops and collection loops, or horizontal rows composed of floating lines and loops. Among them, in one organizational cycle, the number of horizontal rows formed by the yarns of the A layer and the yarns of the B layer is not particularly limited and can be adjusted according to actual needs.

[0017] In one weave cycle, at least one horizontal row is formed by weaving the yarns of layer A and layer B together in the same weaving method, that is, the yarns of layer A and layer B are located in the same horizontal row of coils, and each horizontal row of layer A has the tightening effect of layer B yarn, so that the raised coils on the fabric will be tighter, flatter, and have better anti-snagging performance. This design not only makes the coil pores of layer A smaller, the coil arrangement is more compact, and reduces the possibility of layer C yarn being exposed to layer A, making the fabric more waterproof, but also makes the yarn less likely to be hooked out, giving the fabric excellent anti-snagging performance.

[0018] In a weave cycle, if a horizontal row is not formed by weaving the yarns of layer A and layer B together in the same weaving method, then either the yarns of layer A and layer B form a row of coils arranged one after another on the fabric, or the coils formed by the yarns of layer A and layer B are arranged together on the fabric to form a row of coils. In these two cases, due to the different shrinkage rates of the yarns of layer A and layer B, the coils of the obtained fabric are loose and of different sizes, and the gaps between the coils are large, which greatly affects the anti-snagging property of the fabric. In addition, the yarns of layer C outside layer A are connected with the yarns of layer A through weaving. Since the coils of layer A are loose, the possibility of the yarns of layer C being exposed in layer A increases, which affects the anti-snagging property of the fabric.

[0019] The yarn of layer A of the present invention includes yarn A1 containing more than 8.0 weight % of inorganic particles. This is because inorganic particles have a scattering effect on incident light, which can hinder the transmission of light and reduce the transmittance of light. When inorganic particles are added to the fiber, the reflection interface inside the fiber can be increased, and the fabric is wetted by water, and the color will not change much. However, the higher the content of inorganic particles added to the fiber, the lower the breaking strength of the yarn. When the content of inorganic particles in the yarn A1 is more than 8.0 weight %, the waterproof effect of the fabric is good. The water marks here refer to the marks after wetting, which can be the marks after wetting by rain, sweat, tap water, etc. The waterproof effect means that it is difficult to see the water marks in layer A of the pointer fabric, or the water marks disappear quickly after they appear and become invisible. When the content of inorganic particles in yarn A1 is greater than 20.0 weight %, there are problems of poor engineering passability and poor yarn spinnability. Therefore, it is more preferred that the yarn of layer A includes yarn A1 containing 8.0 to 20.0 weight % of inorganic particles.

[0020] The A-layer yarn in the present invention may include, in addition to the yarn A1, yarns A2, A3, etc. The raw materials of the yarns A2, A3, etc. may be selected from ordinary polyester (ordinary PET), polyamide (NY6), etc. Considering the excellent waterproof effect of the fabric, the raw materials of the yarns A2, A3, etc. are preferably fully matte ordinary polyester (ordinary PET).

[0021] The loops formed by A1 of the present invention account for more than 30% of the total number of loops in the A layer. This is because if the loops formed by the yarn A1 account for less than 30% of the total number of loops in the A layer, the yarn A1 is less exposed on the layer, the amount of reflected light before and after wetting changes greatly, and the color looks darker. More preferably, the loops formed by A1 account for 100% of the total number of loops in the A layer.

[0022] In the present invention, the product J of the transverse and longitudinal density of the fabric and the breaking strength Q of the yarn A1 satisfy the following relationship: J / Q≥1200. Wherein, J represents the product of the transverse density and the longitudinal density of the fabric, where the transverse density refers to the number of longitudinal rows of coils per inch length along the transverse direction of the fabric (unit: pieces / inch); the longitudinal density refers to the number of transverse rows of coils per inch length along the longitudinal direction of the fabric (unit: pieces / inch). The breaking strength Q represents the breaking strength of the yarn (unit: cN / dtex). Considering the anti-snagging performance of the fabric, the density product J is preferably an integer greater than 3000. Considering the wearing performance of the fabric, the transverse density of the fabric is preferably 50-70 pieces / inch, the longitudinal density is preferably 60-85 pieces / inch, and the yarn breaking strength Q is preferably above 2.5 cN / dtex.

[0023] Considering that when the content of inorganic particles in yarn A1 is more than 8.0 weight%, although the fabric has a good anti-watermarking effect, it will affect the breaking strength of yarn A1. When J / Q ≥ 1200, the coils of the fabric are arranged closely, the fabric is compact, the yarn A1 is not easy to be hooked out, and the fabric has strong anti-snagging properties. In other words, in order to obtain a fabric that has both waterproof and anti-snagging effects, not only should yarn A1 with an inorganic particle content of more than 8.0 weight% be selected, the coils formed by A1 should account for more than 30% of the total number of coils in layer A, and in one tissue cycle, at least one horizontal row is woven together by the yarns of layer A and layer B and formed in the same weaving method. The fabric obtained in this way is compact and has good anti-snagging properties.

[0024] If the relationship J / Q is less than 1200, the coils on the fabric are sparsely arranged. On the one hand, the coils are larger, and the yarn A1 is more easily hooked out or even broken, resulting in poor anti-snagging performance. On the other hand, when the coils of the A layer are larger, the relatively curled single fibers in the C layer yarn can easily be exposed from the pores in the middle of the coils or the gaps between the longitudinal rows of coils, causing the C layer yarn to be hooked out in the A layer, and the anti-snagging performance of the fabric becomes poor. In addition, the exposure of the C layer yarn in the A layer will also affect the waterproof effect of the fabric of the present invention.

[0025] Preferably, the C layer of the single-sided knitted fabric of the present invention has a concavo-convex structure, and the protrusion height of the concavo-convex structure is 20 to 100 μm. This is because within this range, the C layer of the fabric can form point contact with the skin, and the dryness of the skin surface is better. When the height of the protrusion is less than 20 μm, the skin and the fabric are likely to form a large area of ​​surface contact. When the human body sweats, a water film is likely to form between the fabric and the skin, and the skin tends to be sticky, so it is not preferred. When the protrusion height is higher than 100 μm, the path for the fabric to conduct sweat and moisture becomes longer, and the dryness of the skin surface tends to decrease, so it is not preferred.

[0026] Preferably, the inorganic particles contained in the yarn A1 of the present invention are one or more of titanium dioxide, aluminum oxide, antimony trisulfide, zirconium oxide, cadmium red, and calcium oxide. Considering that titanium dioxide has a good light scattering effect and has good safety, stability, and dispersibility, it is more preferred.

[0027] The form of the A layer yarn and the B layer yarn in the present invention is not particularly limited, and preferably is filament. Among them, considering the softness of the fabric, the filament used in the A layer is more preferably DTY. Considering the low cost and wide range of use of polyester, polyester DTY is further preferred.

[0028] Preferably, the residual torque of the B-layer yarn in the present invention is 0, this type of yarn has not been subjected to false twisting, and the single fiber state is very straight. Considering that the single fiber of FDY is in a straight state and has a strong ability to conduct moisture, when the B-layer yarn is in the form of FDY, the water absorption and quick-drying properties of the fabric tend to be improved, so it is more preferred. Considering that high-shrinkage yarn can give the fabric a compact effect, it is further preferred that the B-layer yarn is high-shrinkage FDY. The high-shrinkage FDY here refers to filaments in the form of FDY with a boiling water shrinkage rate of more than 30%. When the B-layer yarn is high-shrinkage polyester FDY, its high shrinkage characteristics can give the A-layer of the fabric a more compact effect, and the anti-snagging and water absorption and quick-drying properties of the fabric tend to be improved.

[0029] Preferably, the melting enthalpy of the yarn of layer B of the present invention is below 40 J / g. This is because when the melting enthalpy of the yarn is below 40 J / g, the yarn has a low crystallinity, a loose molecular arrangement, a large heat shrinkage rate, a tendency to improve the compactness of the fabric, and good anti-snagging performance. When the melting enthalpy of the yarn forming layer B is greater than 40 J / g, the crystallinity of the yarn is higher, the molecular arrangement is more orderly, and the heat shrinkage rate of the yarn tends to decrease, resulting in insufficient compactness of the fabric and a tendency to deteriorate anti-snagging performance. That is, the coils of layer A are not tightened enough, the gaps between the longitudinal rows of coils become larger, the pores in the coils become larger, and the yarns are more easily hooked, resulting in poor snagging; at the same time, because the pores in the coils of layer A become larger, the yarns of layer C pass through the pores of the coils of layer A and are exposed in layer A, which increases the possibility of poor waterproofing of the fabric, and is therefore not preferred.

[0030] Preferably, the yarn of the C layer is selected from one or more of polybutylene terephthalate monocomponent fiber (PBT), polytrimethylene terephthalate monocomponent fiber (PTT), polybutylene terephthalate / polyethylene terephthalate composite fiber (PBT / PET), polytrimethylene terephthalate / polyethylene terephthalate composite fiber (PTT / PET), and high-viscosity polyethylene terephthalate / low-viscosity polyethylene terephthalate composite fiber (PET). Considering that the curling performance of polybutylene terephthalate (PBT) fiber is very good, PBT fiber can form a larger arc after curling, which can be used as the contact point between the skin and the fabric, more effectively reducing the contact area between the skin and the C layer of the fabric, forming point contact, giving the skin a drier touch, and reducing the sticky feeling between the fabric and the skin when sweating a lot; and the curled structure makes the gaps between the single fibers larger and the capillary diameter thicker. According to the capillary differential effect, the water conduction rate tends to be accelerated, the moisture content of the inner layer is further reduced, and the dryness of the inner layer of the fabric tends to be improved. Therefore, it is more preferred.

[0031] The fineness of the yarn forming the fabric of the present invention is not particularly limited, wherein the fineness of the yarn of the A layer is preferably 30 to 200 deniers (hereinafter referred to as D); the fineness of the yarn of the B layer is preferably 20 to 140D; the fineness of the yarn of the C layer is preferably 30D to 80D, more preferably 30D to 40D. Considering the waterproof effect of the fabric, the fineness of the yarn of the A layer is preferably greater than the fineness of the yarn of the B layer and the C layer; considering the water absorption and quick-drying performance of the fabric, the fineness ratio of the single fiber of the yarn of the A layer to the single fiber of the yarn of the B layer is preferably less than 1, so that a capillary effect can be generated between the yarn of the A layer and the yarn of the B layer, and the moisture is more easily conducted and diffused from the skin surface to the surface layer, and the drying speed is faster.

[0032] In the present invention, the fiber raw material of yarn A1 is not particularly limited, and can be ordinary polyester (ordinary PET), modified polyester, polyamide (NY6), etc. The cross-sectional shape of the fiber is also not particularly limited, and can be circular, triangular, cross-shaped, etc. The composite form of the fiber can be core-sheath, multi-layer, etc. Such a composite form can maximize the content of inorganic particles. For example, in a core-sheath structure, the inorganic particles are mainly concentrated in the core, which is conducive to weaving and can reduce the friction between the yarn and the weaving equipment. Therefore, the core-sheath structure is preferred.

[0033] Taking into account the dry performance of the fabric surface, the single-sided knitted fabric of the present invention preferably has a C layer formed by a weaving method in which the tuck units and the float units are alternately distributed.

[0034] Considering the water absorption and quick-drying performance of the present invention, the single-sided knitted fabric of the present invention is preferably processed with a water-absorbing resin. The water-absorbing resin can be a polyester resin, an acrylic resin, etc. The water-absorbing resin can be processed by absorbing water in a bath or during post-finishing.

[0035] The structure of the single-sided knitted fabric of the present invention is not particularly limited, but the A layer is preferably a single-sided structure with a plain appearance or a pique appearance.

[0036] The present invention will be further described below with reference to the embodiments and comparative examples.

[0037] The test methods of various parameters involved in the present invention are as follows:

[0038] To ensure the accuracy of the experimental data, the samples used in the following tests were kept in a constant temperature and humidity environment (65±4%RH, 20±2℃) for more than 12 hours before testing.

[0039] (1) Fabric density product J

[0040] ①Cut a piece of flat, wrinkle-free fabric of about 15cm×15cm as a sample;

[0041] ② Select different positions on the sample and use a density microscope (magnification: 20 times) to mark 3 1 inch × 1 inch squares along the horizontal direction of the fabric coils;

[0042] ③ Under a microscope (magnification: 30 times), confirm the number of coils in the three marked squares along the horizontal direction of the coils, and obtain three data. The average value is the horizontal density W of the sample.

[0043] (Unit: pieces / inch);

[0044] ④ Under a microscope (magnification: 30 times), confirm the number of coils in the three marked squares along the longitudinal direction of the coils, and obtain three data. The average value is the longitudinal density C of the sample.

[0045] (Unit: pieces / inch);

[0046] ⑤The density product J of the fabric can be calculated according to the following formula:

[0047] J=W×C

[0048] (2) Yarn breaking strength Q

[0049] Cut 3 pieces of fabric about 30cm×20cm flat and wrinkle-free as sample fabrics. Disassemble 10 yarns to be tested from each sample fabric, for a total of 30 yarns to be tested. During the disassembly process, pay attention to keep the yarns in a natural tension-free state. First, take one of them and clamp both ends of the yarn to be tested on the fixture of the constant speed elongation tensile tester (manufacturer: INTEC CO., LTD. Osaka Japan, equipment name: UNIVERSALTENSILE STRENGTH TESTER). The clamping distance between the upper and lower ends is 200mm. The initial load is calculated according to the yarn fineness. The calculation formula for the initial load is: initial load (unit N) = yarn fineness (denier: D) × 0.1g / D × 10 -2 , stretch the yarn at a speed of 200 mm / min in a direction perpendicular to the horizontal plane until the yarn breaks. The data displayed on the computer connected to the stretching device is what you want. In the same way, test the breaking strength of the remaining 29 yarns, and take the average of the 30 data as the breaking strength of the yarn to be tested, in cN / dtex.

[0050] (3) Determination of inorganic particle content in yarn A1

[0051] ① Cut a smooth, wrinkle-free sample of about 15cm×15cm, remove the different yarns in layer A of the fabric, and determine the yarn A1 and other yarns in the fabric based on the results of the yarn breaking strength test;

[0052] ② Melting sample preparation: Take 4g (±0.1g) of A1 yarn and put the yarn to be tested into a special standard aluminum pan that matches the size of the sample placement table of the X-ray fluorescence spectrometer (manufacturer: Rigaku, model: ZSX PrimusⅢ+). When the heating table is heated to about 360℃, place the aluminum pan on the heating table to melt the yarn;

[0053] ③ When the yarn sample to be tested in the aluminum pan is in a molten state, place the aluminum pan containing the molten liquid in the specified position of the sample making machine and press it into a cake-shaped solid;

[0054] ④ Place the aluminum plate containing the cake-shaped solid sample to be tested into the specified position of the testing instrument, and determine the content of metal elements therein by X-ray fluorescence spectrometer;

[0055] ⑤ Calculate the content of inorganic particles in the yarn through the molecular formula.

[0056] (4) The proportion of the coils formed by yarn A1 to the total coils in layer A

[0057] ① Cut a smooth, wrinkle-free sample of about 15cm×15cm, remove the different yarns in the fabric, and determine the yarn A1 and other yarns in the fabric based on the results of the determination of the inorganic particle content in the yarn;

[0058] ② In the weave structure of a complete weave loop of the fabric, mark the flower height (vertical) and flower width (horizontal) of a weave loop;

[0059] ③ Cut a flat, wrinkle-free sample containing at least one complete tissue cycle, and confirm the number of loops of each yarn on the surface. The proportion z of yarn A1 can be calculated according to the following formula:

[0060] z=x / y×100%

[0061] Where x: the number of loops formed by yarn A1 on this surface

[0062] y: The total number of coils in a complete tissue cycle on the surface is sampled 5 times, and the average of the 5 results is taken as the final result.

[0063] (5) Residual torque

[0064] Cut 3 pieces of flat, wrinkle-free fabrics of about 60cm×30cm as sample fabrics. Disassemble 10 yarns to be tested from each sample fabric, ensuring that the length of each yarn under tension is 1 meter or more, for a total of 30 yarns to be tested. During the disassembly process, pay attention to keep the natural tension-free state. Fix the two ends of the disassembled yarn with tape to avoid untwisting. According to the fineness of the yarn, calculate the required tension of the yarn to be tested according to 0.002g / D. Hang the initial load in the central part, and the yarn will begin to rotate due to the tendency of untwisting, forming twisted yarns until it stops. The yarn after stopping is tested on the twist tester (Y301A) by untwisting method to test the twist number (T / m). In the same way, test the remaining 29 yarns, and take the average of the 30 data obtained as the residual torque of the yarn to be tested, unit T / m.

[0065] (6) Melting enthalpy

[0066] Using a differential scanning calorimeter (DSC2A-01820), refer to GB / T 40271-2021 standard to perform DSC test on the yarn to be tested and obtain the DSC curve. Mark the melting point peak temperature on the DSC curve to obtain the melting enthalpy. The result is accurate to one decimal place, unit: J / g.

[0067] (7) Waterproof effect

[0068] According to Q / 320691TTC02-2020 immersion test, the specific method is as follows:

[0069] ① Cut 4 smooth, wrinkle-free 5cm×5cm samples, place them in an environment with a temperature of 20±2℃ and a humidity of 65±4% for 24 hours to adjust the humidity, and obtain the dry samples. Weigh the mass of the dry sample fabric as H1;

[0070] ② Randomly select one of the samples as a blank control sample, and the remaining three samples as test samples for testing. Quickly immerse one test sample in the test liquid (grade 3 water) and start timing. After 60 seconds, take out the sample and weigh it when it stops dripping and count it as H2 (sample non-drip state: the time difference between 2 drops of water is more than 10 seconds to be judged as non-drip).

[0071] ③ Calculate the liquid content H of the sample according to the following formula.

[0072] Liquid content H (%) = (H2-H1) / H1×100%

[0073] m1: dry mass of 5cm×5cm sample;

[0074] m2: The mass of the sample that does not drip after immersion for 60 seconds;

[0075] ④ After weighing, place the sample on a glass plate and use GB / T 250-

[0076] 2008 Color Change Use Gray Card to judge the color difference with the comparison sample and record the grade. Reference for the use of standard light box: TFRCTEST-0155-048 Standard Light Box Operating Procedure or TFRCTEST-0155-104 Standard Light Box (Color Matching Light Box) Operating Procedure.

[0077] ⑤The evaluation criteria are as follows

[0078] Superior products Qualified products Defective products Sweat rate H (%) ≥100 ≥100 <100 Wet discoloration grade ≥4 3-4 <3-4

[0079] ⑥ Test the remaining two test samples separately in the same way, and obtain three sets of data in total. Take the average value of the three test results as the wet discoloration grade evaluation result of this sample, and record it as the evaluation result of the waterproof mark resistance effect of this sample.

[0080] (8) Raised height

[0081] Cut a smooth, wrinkle-free fabric of about 20cm×20cm as a sample, and use the skin-contacting surface of the fabric as the test surface. Use a KEYENCE VHX-2000C microscope to observe the test surface. Place the test surface of the fabric at the observation point, adjust the microscope magnification to 150 times, perform deep synthesis and 3D display on the observation point, read the height between the zero starting point and the highest point of the bulge in the 3D display image, and obtain 1 data of the bulge height. According to the above method, perform deep synthesis and 3D display on 10 points of the test surface respectively, and obtain a total of 10 data. Remove the two largest data and the two smallest data to obtain the 6 data in the middle, calculate the average value, and the obtained average value is the bulge height (in μm).

[0082] (9) Snag

[0083] The test and rating are carried out according to condition B of GB / T 11047-2008 (hammer method). The rating is divided into 1 to 5 levels (intermediate levels such as 1.5 are acceptable), with a total of 9 levels. The results are retained to one decimal place. The higher the rating result, the better the anti-snagging property.

[0084] (10) Water retention ratio of the surface and the inside

[0085] ① Take 3 pieces of 10cm*10cm sample cloth, 6 pieces of filter paper of the same size, and 1 piece of plexiglass of the same size;

[0086] ②In an environment with a temperature of 20±2℃ and a humidity of 65±4%, adjust the temperature and humidity for 24 hours;

[0087] ③ First weigh the weight of a piece of sample cloth (W1) (keep three decimal places) and the weight of the two filter papers before absorbing water (w1, w3) (keep three decimal places), then use a syringe to measure 1mL of tertiary water and place it on the plexiglass, and quickly place the weighed sample cloth (test surface facing down) on the water. After leaving it for 1 minute, weigh the weight of the sample cloth after absorbing water (W2) (keep three decimal places); then, place the sample cloth after absorbing water (test surface facing down) between the two filter papers, and place a 500g weight on the filter paper. After leaving it for 1 minute, directly weigh the weight of the surface filter paper and the inner filter paper (w2, w4) (keep three decimal places), and calculate the surface and inner water retention rate ratio (keep one decimal place) by the following formula:

[0088] Surface water retention rate (%) = (w2-w1) / (W2-W1)×100

[0089] Internal water retention rate (%) = (w4-w3) / (W2-W1)×100

[0090] Surface water retention ratio = surface water retention (%) / inner water retention (%)

[0091] W1: weight of the sample cloth before absorbing water (g)

[0092] W2: Weight of the sample fabric after absorbing water (g)

[0093] w1: Weight of filter paper on the surface before water absorption (g)

[0094] w2: Weight of the filter paper on the surface after absorbing water (g)

[0095] w3: Weight of the filter paper before absorbing water (g)

[0096] w4: The weight of the filter paper inside after absorbing water (g)

[0097] ④ Measure the remaining two pieces of fabric samples according to the method in step c, and take the average value as the surface and inside water retention ratio of the present invention.

[0098] The greater the ratio of surface to inner water retention rate, the drier the fabric surface.

[0099] (11) Evaporation rate

[0100] Tested according to GB / T 21655.1-2008.

[0101] The greater the evaporation rate, the better the water absorption and quick-drying properties.

[0102] The present invention will be further described below by way of examples and comparative examples.

[0103] Example 1

[0104] 50D / 36f PET DTY (8.0 wt% titanium dioxide inorganic particles, core-sheath structure) was selected as the yarn A1 of the A layer yarn, 30D / 12f high shrinkage PET FDY (residual torque of 0 T / m, melting enthalpy of 30 J / g) was selected as the yarn B, and 40D / 24f PBT DTY was selected as the yarn C. On a 32G single-sided circular knitting machine, the yarn was knitted with the attached Figure 2 The variation structure shown in the figure is woven, and the 1st and 3rd paths are configured with yarn A1 and yarn B. The yarn A1 is completely covered on the top of yarn B by adjusting the length of the yarn. The 2nd and 4th paths are configured with yarn C so that the loop ratio of yarn A1 in the A layer is 100%, and the grey cloth is obtained. Then the grey cloth is pre-treated (scouring agent 1g / L, 90℃*20min), dyed (disperse dye 3% owf, 130℃*30min), resin processed (dyeing in the same bath, polyester hydrophilic resin 5g / L, 50℃*20min), and finished (160℃*1min) to obtain the present invention with a gram weight of 150g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 1.

[0105] Example 2

[0106] 50D / 36f PET DTY (0.25 wt% titanium dioxide inorganic particles) is selected as the yarn A2 of the A layer, and the yarn configuration is adjusted so that the coil ratio of the yarn A1 in the A layer is 30%, and the coil ratio of the yarn A2 in the A layer is 70%. The rest is the same as in Example 1, and the weight of the present invention is 150g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 1.

[0107] Example 3

[0108] The yarn configuration is adjusted so that the coil ratio of yarn A1 in the A layer is 50%, and the coil ratio of yarn A2 in the A layer is 50%. The rest is the same as in Example 2, and the weight of the present invention is 150g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 1.

[0109] Example 4

[0110] 50D / 36f PET DTY (8.0 wt% of inorganic aluminum oxide particles, core-sheath structure) was selected as the yarn A1 of the A layer yarn, and the rest was the same as in Example 1 to obtain a yarn with a gram weight of 150 g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 1.

[0111] Example 5

[0112] 50D / 36f PET DTY (12.5 wt% titanium dioxide inorganic particles, core-sheath structure) was selected as the yarn A1 of the A layer yarn, and the rest was the same as in Example 1 to obtain a yarn with a gram weight of 150 g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 1.

[0113] Example 6

[0114] After adjusting the processing conditions, the J / Q ratio of the fabric is 1200, and the rest is the same as in Example 1, and the gram weight of the present invention is 123g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 1.

[0115] Example 7

[0116] The knitting process and post-processing process conditions are adjusted so that the yarn C forms a protrusion with a height of 20 μm near the skin side on the C layer. The rest is the same as in Example 1, and the weight of the present invention is 140 g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 1.

[0117] Example 8

[0118] The knitting process and post-processing process conditions were adjusted so that the yarn C formed a protrusion with a height of 100 μm near the skin side on the C layer, and the rest was the same as in Example 1, and the weight of the present invention was 155 g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 1.

[0119] Example 9

[0120] The knitting process and post-processing process conditions are adjusted so that the yarn C forms a protrusion with a height of 16 μm near the skin side on the C layer, and the rest is the same as in Example 1, and the weight of the present invention is 150 g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 1.

[0121] Example 10

[0122] 50D / 36f PET DTY (18.0 wt% titanium dioxide inorganic particles, core-sheath structure) was selected as the yarn A1 of the A layer yarn, and the rest was the same as in Example 1 to obtain a yarn with a gram weight of 150 g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 1.

[0123] Embodiment 11

[0124] 30D / 12f PET DTY (residual torque of 20T / m, melting enthalpy of 45J / g) was selected as the yarn B of the B layer, and the rest was the same as in Example 1 to obtain a yarn with a gram weight of 160g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 1.

[0125] Example 12

[0126] 30D / 12f PET FDY (melting enthalpy of 40 J / g) was selected as the yarn B of the B layer, and the rest was the same as in Example 1, and the weight of the present invention was 140 g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 1.

[0127] Embodiment 13

[0128] 30D / 12f PET FDY (melting enthalpy of 43 J / g) was selected as the yarn B of the B layer, and the rest was the same as in Example 1, and the weight of the present invention was 140 g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 2.

[0129] Embodiment 14

[0130] Ordinary PET DTY of 40D / 24f is selected as the yarn C of the C layer, and the rest is the same as in Example 1, and the weight of the present invention is 155g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 2.

[0131] Embodiment 15

[0132] 30D spandex (PU) bare yarn is selected as the yarn B of the B layer, and the rest is the same as in Example 1, and the weight of the present invention is 160g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 2.

[0133] Example 16

[0134] On a 36G single-sided circular knitting machine, 30D / 24f high shrinkage PET FDY (residual torque of 0T / m, melting enthalpy of 35J / g) was selected as the yarn B of the B layer, and 30D / 24f PTT / PET DTY was selected as the yarn C of the C layer. Figure 3 The 1st, 2nd, 4th and 5th paths are woven with yarn A1, and the 1st and 4th paths are woven with yarn B. The yarn A1 is completely covered on the top of yarn B by adjusting the yarn length. The 3rd and 6th paths are woven with yarn C so that the proportion of the loops of yarn A1 in the A layer is 100%, and the grey fabric is obtained. The rest is the same as in Example 1, and the weight of the fabric of the present invention is 147 g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 2.

[0135] Embodiment 17

[0136] Select 50D / 36f ordinary semi-dull (titanium dioxide inorganic particles 0.3 weight %) PET-DTY as the yarn A2 of the A layer, 50D / 36f ordinary full-dull (titanium dioxide inorganic particles 2.5 weight %) PET-DTY as the yarn A3 of the A layer, and 30D / 24f ordinary PBT / PET DTY as the yarn C. Adjust the yarn configuration so that the coil ratio of yarn A1 in the A layer is 80%, the coil ratio of yarn A2 in the A layer is 10%, and the coil ratio of yarn A3 in the A layer is 10%, and the grey cloth is obtained. The rest is the same as in Example 16, and the gram weight of the present invention is 145g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 2.

[0137] Embodiment 18

[0138] On a 32G single-sided circular knitting machine, Figure 4 The 1st, 2nd, 4th and 5th paths are woven with yarn A1 and yarn B, and the yarn length is adjusted so that yarn A1 completely covers the yarn B. The 3rd and 6th paths are woven with yarn C. The rest is the same as in Example 1, and the weight of the present invention is 170 g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 2.

[0139] Comparative Example 1

[0140] 50D / 36f PET DTY (5.0 wt% titanium dioxide inorganic particles, core-sheath structure) was selected as the A-layer yarn, and the rest was the same as in Example 1 to obtain a yarn with a gram weight of 150 g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 2.

[0141] Comparative Example 2

[0142] The yarn configuration was adjusted so that the loop ratio of yarn A1 in its A layer was 25%, and the rest was the same as in Example 2, and the gram weight was 150 g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 2.

[0143] Comparative Example 3

[0144] Adjust the yarn configuration so that Figure 2 The first and fourth routes in the structure shown are woven only by yarn B (i.e., the coil rows formed by layer A and layer B are not in the same row), and the rest is the same as in Example 1, and the weight is 122 g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 2.

[0145] Comparative Example 4

[0146] Adjust the yarn configuration so that Figure 2The first and fourth routes in the structure shown are woven only by yarn A1 (i.e., the fabric is a double-layer structure, and there is no B layer formed by yarn B in the fabric), and the rest is the same as in Example 1, and the weight is 112 g / m 2 Single-sided knitted fabric, specific parameters are shown in Table 2.

[0147]

[0148]

[0149] According to Table 1 and Table 2,

[0150] (1) It can be seen from Examples 7 and 9 that, under the same conditions, the single-sided knitted fabric with a concave-convex structure with a protrusion height of 20 μm is superior to the single-sided knitted fabric with a concave-convex structure with a protrusion height of 16 μm in terms of surface-to-inside water retention rate ratio and evaporation rate, and the anti-watermarking effect and anti-snagging property are at the same level.

[0151] (2) It can be seen from Examples 1 and 11 that, under the same conditions, the single-sided knitted fabric formed by using yarn B with a residual torque of 0 T / m and a melting enthalpy of 30 J / g as the B-layer yarn is superior to the single-sided knitted fabric formed by using yarn B with a residual torque of 20 T / m and a melting enthalpy of 45 J / g as the B-layer yarn in terms of waterproofing effect, anti-snagging property, surface-to-interior water retention ratio and evaporation rate.

[0152] (3) It can be seen from Examples 12 and 13 that, under the same conditions, the single-sided knitted fabric formed by yarn B with a melting enthalpy of 40 J / g is superior to the single-sided knitted fabric formed by yarn B with a melting enthalpy of 48 J / g in terms of waterproofing effect, anti-snagging property, surface-to-interior water retention ratio and evaporation rate.

[0153] (4) It can be seen from Example 1 and Example 14 that, under the same conditions, the single-sided knitted fabric formed by using PBT as yarn C has a better surface-to-inside water retention rate ratio than the single-sided knitted fabric formed by using ordinary PET as yarn C, and the evaporation rate, anti-snagging property and waterproof effect of the two are at the same level.

[0154] (5) It can be seen from Example 1 and Example 15 that, under the same conditions, the single-sided knitted fabric using high shrinkage FDY as yarn B to form the middle B layer is compared with the single-sided knitted fabric using spandex bare yarn as yarn B to form the middle B layer. The former has a better surface water retention rate ratio and evaporation rate than the latter, and the anti-snagging and water-proof effects of the two are at the same level.

[0155] (6) It can be seen from Comparative Example 1 and Example 1 that, under the same conditions, the single-sided knitted fabric with an inorganic particle content of 5.0 wt% of yarn A1 is far less waterproof than the single-sided knitted fabric with an inorganic particle content of 8.0 wt% of yarn A1, and their anti-snagging properties, surface and inner water retention rate ratio and evaporation rate are at the same level.

[0156] (7) It can be seen from Comparative Example 2 and Example 2 that, under the same conditions, the single-sided knitted fabric in which the loops formed by yarn A1 account for 25% of the total number of loops in the A layer is far less waterproof than the single-sided knitted fabric in which the loops formed by yarn A1 account for 30% of the total number of loops in the A layer. The surface-to-inside water retention rate ratio, anti-snagging property and evaporation rate of the two are at the same level.

[0157] (8) It can be seen from Comparative Example 3 and Example 1 that the single-sided knitted fabric in which the B-layer yarn and the A-layer yarn form different horizontal rows of coils is inferior to the single-sided knitted fabric in which the B-layer yarn and the A-layer yarn form the same horizontal row of coils in terms of waterproofing effect, anti-snagging property, surface-to-interior water retention ratio and evaporation rate.

[0158] (9) It can be seen from Comparative Example 4 and Example 1 that the two-layer single-sided knitted fabric is inferior to the three-layer single-sided knitted fabric with an intermediate B layer in terms of anti-snagging, waterproofing effect, surface-to-interior water retention ratio and evaporation rate.

Claims

1. A single-sided knitted fabric, consisting of a layer A, a layer B and a layer C, wherein the layer C has a concave-convex structure, characterized in that: In one tissue cycle, at least one horizontal row is formed by weaving the yarn of layer A and the yarn of layer B together in the same weaving method, the yarn of layer A includes yarn A1 containing more than 8.0 weight% of inorganic particles, the coils formed by A1 account for more than 30% of the total number of coils in layer A, and the product J of the transverse and longitudinal density of the fabric and the breaking strength Q of the yarn A1 satisfy the following relationship: J / Q≥1200.

2. The single-sided knitted fabric according to claim 1, characterized in that: The protrusion height of the concavo-convex structure is 20 to 100 μm.

3. The single-sided knitted fabric according to claim 1 or 2, characterized in that: The residual torque of the B layer yarn is 0.

4. The single-sided knitted fabric according to claim 1 or 2, characterized in that: The melting enthalpy of the yarn of the B layer is below 40 J / g.

5. The single-sided knitted fabric according to claim 1 or 2, characterized in that: The yarn of the C layer is selected from one or more of polybutylene terephthalate monocomponent fiber, polytrimethylene terephthalate monocomponent fiber, polybutylene terephthalate / polyethylene terephthalate composite fiber, polytrimethylene terephthalate / polyethylene terephthalate composite fiber, and high-viscosity polyethylene terephthalate / low-viscosity polyethylene terephthalate composite fiber.

6. A sports shirt, T-shirt or POLO shirt made using the single-knitted fabric according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Fabric with function of bidirectional adjustment of heat humidity

    CN102134776A

  • Water-absorbing quick-drying knitted fabric and application thereof

    CN105986358A

  • Knitted fabric and application thereof

    CN115398051A

  • Double-sided knit fabric

    JP2019509407A